Cross‐Coupling of Aryl‐Bromide and Porphyrin‐Bromide on an Au(111) Surface. Issue 22 (16th April 2015) - Kuang, Guowen; Zhang, Qiushi; Li, Deng Yuan; Shang, Xue Song; Lin, Tao; Liu, Pei Nian; Lin, Nian
Abstract Cross‐coupling is of great importance in organic synthesis. Here it is demonstrated that cross‐coupling of aryl‐bromide and porphyrin‐bromide takes place on a Au(111) surface in vacuo. The products are oligomers consisting of porphyrin moieties linked by p‐phenylene at porphyrin's meso‐positions. The ratio of the cross‐coupled versus homocoupled bonds can be regulated by the reactant concentrations. Kinetic Monte Carlo simulations were applied to determine the activation barrier. It is expected that this reaction can be employed in other aryl‐bromide precursors for designing alternating co‐polymers incorporating porphyrin and other functional moieties.